Peran Manajemen Menguatkan Budaya, Etika dalam Pengelolaan Sampah di Kota Bandung - Hari Imbrani; Abdul Patah; Wati Rahayu (Lembaga Pengembangan Kinerja Dosen, 2025)
Air pollution and damage to the earth are central world problems and are threats that will occur if humans continue to cause damage to this earth. Pollution on earth is very clear is the increasing amount of organic and non-organic waste, in activities to meet the needs of society, the end result is waste, both waste generated from the needs of clothing, food and shelter, if not handled properly and correctly will threaten the survival of society and threaten the ecology in the world, Organic and non-organic waste must be handled with good management. Management as a tool for organizational management in a society is expected to play an important role in providing education and understanding to the community about the impacts and dangers caused by the increase in waste due to human activities, so that it can strengthen the culture and ethics of society in managing waste so that it will increase the creative abilities of society, creativity, taste and intention in managing waste. The type of research conducted by the author is included in the category of qualitative research literature study method researchers to collect and evaluate information from various previous studies, thus providing a comprehensive understanding of the subject under study.